Improving Students' Memorization Ability in Islamic Education Learning through the Drill Method at SMA Negeri 2 Painan - Nafrianto, Dori (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve students' memorization skills in Islamic education learning using the Drill Method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. The test is used to measure the increase in students' memorization skills in Islamic education learning and observation is used to analyze the learning activities of teachers and students. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the Drill Method can improve student learning outcomes in Islamic education learning. This can be seen from the increase in the percentage of completeness of improving students' understanding abilities in each cycle with details of the pre-cycle 48.56%, the first cycle 67.47% and in the second cycle it increased to 91.57%. Thus, the use of Drill can be used as an alternative to increase student activity in Islamic education learning in Islamic education learning.